Familial amyotrophic lateral sclerosis with novel A4D SOD1 mutation with late age at onset and rapid progressive course. Issue 1 (31st January 2013) - Naruse, Hiroya; Iwata, Atsushi; Takahashi, Yuji; Ichihara, Kazuaki; Kamei, Satoshi; Yamatoku, Masato; Hirayama, Toshikazu; Suzuki, Naoki; Aoki, Masashi; Miyagawa, Toji; Shimizu, Jun; Tsuji, Shoji; et al.
Abstract Our objective was to obtain clinical presentations of familial amyotrophic lateral sclerosis (FALS) with a novel Ala4Asp (A4D) SOD1 mutation in a Japanese family and to determine the epidemiological features of the SOD1 mutation on the basis of the ALS mutation database. The clinical histories and neurological findings of three affected individuals in a Japanese FALS pedigree are described. DNA analysis of SOD1 was conducted by a direct nucleotide sequence analysis. We identified a novel heterozygous A4D mutation in exon 1 in SOD1. The clinical presentations of the family were characterized by late age at onset and rapid progression. Comprehensive analysis of genotype‐phenotype correlations using the ALS mutation database revealed that all the patients with SOD1 amino acid 4 mutations tended to have a rapid progressive course of the disease with a duration of 1.27 years. The age at onset varied among SOD1 amino acid 4 mutations, but all three patients with A4D mutation had a very late age at onset of over 70 years. In conclusion, FALS patients with a novel A4D mutation in SOD1 showed a late age at onset with a rapid disease course. This study supports the previous observations that SOD1 amino acid 4 mutations contribute to the acceleration of disease progression and emphasizes the usefulness of the ALS mutation database.